Intuitive eating is associated with weight loss after bariatric surgery in women. Issue 1 (4th June 2019) - Nogué, Muriel; Nogué, Erika; Molinari, Nicolas; Macioce, Valérie; Avignon, Antoine; Sultan, Ariane
ABSTRACT: Background: Although the data on eating behavior after bariatric surgery are substantial, data on "intuitive eating" are lacking. Objective: The aim of this study was to evaluate the link between intuitive eating and weight loss after bariatric surgery. Methods: This cross-sectional study used a self-administered questionnaire freely available on social networks and targeted women who had undergone bariatric surgery. Intuitive eating was evaluated with the Intuitive Eating Scale-2 (IES-2). The 3 questionnaire subscores (Eating for Physical Rather than Emotional Reasons, Reliance on Hunger and Satiety Cues, and Unconditional Permission to Eat) were also analyzed. The relation between IES-2 scores and the relative variation in body mass index [BMI (in kg/m 2 )] was assessed with linear regression models. Adjusted β (βAdj ) and standardized β ( β _Adj^STD ) were reported. Results: We analyzed the responses of 401 women with a mean age of 39 ± 11 y, a mean preoperative BMI of 45.5 ± 7.9, and a mean current BMI of 30.5 ± 7. The mean relative BMI loss was 32.7 ± 12.9%, and the mean IES-2 score was 3.3 ± 0.6. The total IES-2 score was associated with the relative BMI loss, with ∼2.6% BMI loss for each 1-point increase in the IES-2 score [ P Adj = 0.007; βAdj = −2.57 (95% CI: −4.44, −0.70); β _Adj^STD = −0.12] after adjusting for elapsed time since surgery and type of surgery. Eating for Physical Rather than Emotional Reasons was the subscore most strongly associated with BMI change after adjustment [ P Adj = 0.002; βAdj = −2.08 (95% CI: −3.37, 0.79); β _Adj^STD = −0.14]. Conclusions: This study highlights a significant association between intuitive eating and BMI decrease after bariatric surgery. Furthermore, eating behaviors changed with increasing time since surgery. An intuitive nutritional approach may be complementary with bariatric surgery in the postoperative phase, which should prompt complementary prospective studies to evaluate the effectiveness of therapeutic education programs centered on intuitive eating in the postoperative period.